Perinatal period affecting neuropsychic state of children in Arctic zone - N. L. Solovevskaya; N. K. Belisheva; S. V. Pryanichnikov (Акушерство, гинекология и репродукция, 2023)
Aim: to identify potential causes accounting for development or predisposition to congenital neuropsychiatric disorders (NPD) in childhood and assessing an opportunity for conducting preventive interventions to lower a risk of childbirth coupled to congenital malformations.Materials and Methods. The pediatric medical records with NPD and psychomotor retardation were analyzed: data on the pattern of pregnancy and maternal delivery-related complications as well as delivery-associated complications and fetal developmental abnormalities, the maternal morbidity pattern before and during pregnancy; data on paternal health state as well as available social information about parents were also assessed.Results. It was revealed that potential causes for delivery of children with NPD and subsequent development of psychomotor retardation were due to complications during pregnancy such as infections of pregnant women, gestosis, anemia; among maternal complications in childbirth of special attention were long anhydrous period as well as surgical interventions.Conclusion. The course of pregnancy and childbirth as well as emerging neonatal pathology may be also influenced by the climatic and meteorological conditions of the Arctic zone causing Arctic hypoxia. Significant correlations between solar wind parameters and morbidity of pregnant women may indicate a need for more extensive studies regarding effects of geocosmic factors on course of pregnancy, childbirth and fetal gestation.